Investor Behavior In Green Investment Information - Puspitasari, Intan; Wahyudi, Sugeng; Pangestuti, Irene Rini Demi (AL-ARBAH: Journal of Islamic Finance and Banking, 2020)
AbstractPurpose - This study aims to analyze the behavior of investors towards voluntary disclosure in the form of green investment information.Method - This research is using qualitative descriptive method, the data will be taken and collected from several literatures and literature studies.Result - The result of this research indicates that there are investors’ behaviors in voluntary disclosure of green investment information.The first, green investor refers to the investors rejecting to the stocks that do not receive green investment, investor will react positively if a disclosure of green investment information stands.The second, the investors react negatively by giving pessimistic respond towards green investment, investors who do not have choice of shares from other companies.Implication - This study uses the data from study of literature.Originality - This research develops several old and new theories related to green investment and it is applied using certain different types of companies as the objects.